Oesophageal candidiasis after omeprazole therapy. Issue 6 (June 1992) - Larner, A J; Lendrum, R
Abstract : Oesophageal candidiasis was diagnosed incidentally at endoscopy in two patients receiving omeprazole therapy. There were no other predisposing factors for the development of candidiasis. The infection was resolved rapidly by anti-candidal therapy and by stopping omeprazole. These findings suggest that gastric acid secretion and physiological reflux of acid into the oesophagus may play a protective role in preventing candida infection.